The linguistic analysis of the argumentative speech: (Shimon Peres for example) - Judeh, Ayat Salem; Abd, Rahim Radi (Al-Adab Journal, 2022)
Argumentation is one of the important topics that have received wide attention among linguists, as it contains rhetorical, semantic and pragmatic means, and its connection with daily life through its use in political speeches that are a link between the politician and the public through influence and then persuasionHence, we selected a set of the speeches of Israeli President Shimon Peres, and analyzed them linguistically.This research is concerned with studying argumentation in general and the linguistic methods in particular since the subjects of argumentation are rich in linguistic styles, such as argumentation questions, metaphors, similes, argumentation links, etc.From a linguistic point of view, the research was interested in the rhetorical methods in the Hebrew language, in order to identify the most important functions that they perform in argumentation.The research concluded that the political speeches of Shimon Peres included most of the rhetorical methods in the Hebrew language, employing them in terms of argumentation, and using those arguments in political speeches for the purpose of direct influence on the recipient and then convincing him of the idea to be conveyed in time and space